Comparing the accuracy of linear measurements in different image views of Galileos cone-beam computed tomography unit - Sajad Ghorbanizadeh; Mehrdad Abdinian; Reyhaneh Faghihian; Hossein Goroohi (SRM Journal of Research in Dental Sciences, 2016)
Objectives: The aim of this study was to compare the accuracy of linear measurements in axial, cross-sectional, and tangential cone-beam computed tomography. (CBCT) images in dry human skulls. Materials and Methods: Six dry human skulls were included in the study. Opaque markers were attached to the alveolar bone. Buccolingual and mesiodistal distances and height were measured in 5 different regions by a digital caliper. (Guanglu, Taizhou, China). Radiographic measurements were made in tangential, cross-sectional, and axial CBCT images. To determine the accuracy of linear measurements, the physical and radiographic measurements were compared. Intraclass correlation coefficient, Wilcoxon, one-sample t-test, and univariate analysis of variance were used to analyze the data. Results: The differences between physical and radiographic measurements were not clinically significant in any of the views. (P < 0.05). Conclusions: By opaque markers, the accuracy of measurements in Galileos CBCT machine is adequate in all CBCT image views.